A Non-Isolated Bidirectional DC–DC Converter for Electric Trains With Regenerative Braking Operation - M. R. Banaei; A. H. Lotfollahpour; M. A. Younis; A. Quteishat; H. Afsharirad; A. Safari (Journal of Electrical and Computer Engineering)
Improving the energy conservation through regenerative braking enhances the overall efficiency of the electric transportation system. In order to accomplish this purpose, the most significant function is played by bidirectional power electronics converters. This research proposes a nonisolated bidirectional DC–DC converter (BDC) for electric trains that is capable of converting energy from storage devices to the traction motor side and vice versa in an efficient manner. Furthermore, the simplicity structure, low volume and weight, low cost, and the straightforward switching strategy make it an excellent choice for many high-power applications such as electric trains. An analysis of the converter and a comprehensive discussion of the proposed scheme are presented. Additionally, a 100 W experimental prototype is developed and tested. Simulation and experimental results are highly compatible with the theoretical analysis that validates the proper functionality of the converter.